Visibility of the phantom array effect according to luminance, chromaticity and geometry. (May 2020) - Park, SW; Lee, C-S; Kang, HR; Pak, HS; Wilkins, A
Light-emitting diode-based lighting systems are now applied in both general lighting and automotive lighting. Time-modulated control methods such as pulse width modulation are frequently applied as a dimming method. This paper presents the characteristics of the visibility of the phantom array effect according to luminance, chromaticity and angular field of view. The threshold frequency of the visibility of the phantom array increases in proportion to the logarithm of the luminance of the light source. As the angular field of view of the light source increases, the threshold frequency of the visibility of the array decreases exponentially over a range from 0.125° to 4° in our experimental conditions. The threshold frequency at which the array is visible depends on chromaticity at high light source modulation frequencies. When designing time-modulated light sources, our findings can be applied so as to minimize the phantom array effect.